Żydzi jako wiejscy dzierżawcy karczm w XIX wieku - Gawryszczak, Anna (Zeszyty Wiejskie, 2012)
The aim of this article is first of all an attempt to bring the part of the Jewish community that dealt with the lease and rural inn running closer to readers. The authors tried also to present their economic activity in the light of legally binding regulations in the areas of three partitioning countries. They attempted to describe the specificity of the way the Jews ran rural inns, their grooming and functioning. Moreover, the article presents the characterization of an inn owner who was not necessarily of the Jewish origin and definitely was one of the most important figures in the Polish village community. The paper also describes the process of gradual disappearance of the Jewish arendars, which was closely related to the emergence of a new social class. The consequence of this process was an utter exclusion of the Jews from their arendas, as a result of which they abandoned the countryside and moved to towns.